The Effect Of Progressive Muscle Relaxation and Slow Deep Breathing Combinations on Sleep Quality of Pregnant Women - Mufidah Sheena Andani Prastini; Lilik Herawati; Endyka Erye Frety; Aditiawarman Aditiawarman (Universitas PGRI Palembang, 2022)
Several studies suggest that poor sleep quality has an impact on both the mother and the fetus. Providing relaxation exercises in the form of progressive muscle relaxation and slow deep breathing can be a non-pharmacological effort to improve sleep quality in pregnant women. This study aims to analyze the effect of a combination of progressive muscle relaxation and slow deep breathing in pregnant women of third trimester. This research method is pre-experimental designs with a pretest-posttest control group design. The number of samples was 24 pregnant women trimester III with the sampling technique using consecutive sampling. The independent variable is the provision of progressive muscle relaxation and slow deep breathing exercises which are carried out for 3 times on a week over a period of 3 weeks. The dependent variable is sleep quality which is measured using the Pittsburgh Sleep Quality Index questionnaire. Data analysis used the Wilcoxon signed rank test. The results showed a decrease in the mean value in the direction of improved sleep quality by a difference of 4.5 in the experimental group. Whereas in the control group there was an increase in the value which led to a deteriorating sleep quality by a difference of 1.42. The test results showed a difference in the pretest and posttest of the two groups p = 0.000 (p <0.05). These data indicate that there is an effect of a combination of progressive muscle relaxation and slow deep breathing on the sleep quality pregnant women of third trimester.